DEVELOPMENT OF ONLINE ASSESSMENT FOR 21ST CENTURY LEARNING - Rodniyom, Apichat (Journal of MCU Nakhondhat, 2024)
This academic article presents a guideline for developing online assessment and evaluation models for 21st - century learning. Traditional learning is being challenged by new technologies, and learning assessment and evaluation must evolve alongside these changes. Online assessment and evaluation is a new approach that allows for the effective evaluation of student learning outcomes, addressing the skills needed in the 21st century and responding to the changes in the modern world. 21st-century learning emphasizes a wide range of skills beyond just content knowledge. Traditional assessment and evaluation models cannot effectively evaluate these skills. Online models have the potential to make assessment and evaluation more efficient, support a variety of assessment and evaluation formats, provide real - time feedback to students, and provide immediate feedback to students. This article presents a guideline for developing online assessment and evaluation models, starting with an analysis of the relevant 21st - century learning skills, including higher - order thinking skills, problem - solving skills, creativity, communication skills, collaboration skills, and information and digital literacy skills. The article then considers the appropriate assessment formats for each skill, using assessment and evaluation principles that emphasize the learning process over the outcome and focus on providing feedback to improve student learning. The development of online assessment and evaluation models for 21st - century learning will help to make learning assessment more effective. It will enable the comprehensive and diverse assessment of 21st-century learning skills, allowing students to develop the skills necessary for life and work in the digital age effectively.